Cyclo‐Ketal Xanthene Dyes: A New Class of Near‐Infrared Fluorophores for Super‐Resolution Imaging of Live Cells. Issue 11 (26th January 2021) - Zhang, Xinfu; Chen, Lingcheng; Huang, Zhenlong; Ling, Ni; Xiao, Yi
Abstract: Newly emerging super‐resolution imaging techniques provide opportunities for precise observations on cellular microstructures. However, they also impose severe demands on fluorophores. Here, we develop a new series of NIR xanthene dyes, named as KRh s, by replacing the 10‐position O of rhodamines with a cyclo‐ketal. KRh s display an intense NIR emission peak at 700 nm with fluorescence quantum yields up to 0.64. More importantly, they, without the aid of enhancing buffer, exhibit stochastic fluorescence off–on switches to support time‐resolved localization of single fluorophore. KRh s are functionalized into KRh‐MitoFix, KRh‐Mem and KRh‐Halo that demonstrate mitochondria, plasma membrane and fusion protein targeting ability, respectively. Consequently, these KRh probes demonstrate straightforward usage for super‐resolution imaging of these targets in live cells. Therefore, KRh s merit future development for fluorescence labeling and super‐resolution imaging in the NIR region. Abstract : In this study, the emission of xanthene dye is pushed to the NIR region by replacing the 10‐position O of rhodamines with a cyclo‐ketal. The newly developed KRh s display intense fluorescence peaks at 700 nm ( Φ F 0.64) and, more importantly, exhibit stochastic fluorescence off–on switches to support super‐resolution imaging. These KRh derivatives display great potential for fluorescence labeling and super‐resolution imaging in the NIR region.